The Influence of Knowledge, Perceptions, and E-Banking Facilities on Customer Interest in Using Bank Muamalat Products: Case Study at Bank Muamalat KCP Stabat - Safrina Safitri; Atika Atika; Tuti Anggraini (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
This research aims to determine the influence of knowledge, perceptions, and e-banking facilities on customer interest in using Bank Muamalat products, focusing on Bank Muamalat KCP Stabat. The research method used was a survey by distributing questionnaires to Bank Muamalat KCP Stabat e-banking service customers. Customer knowledge about e-banking is measured through their understanding of the e-banking features offered by Bank Muamalat. Customer perceptions of e-banking are assessed from their views on security, comfort, and service reliability. E-banking facilities are checked based on availability and ease of customer access to services. It is hoped that the results of this research will provide a better understanding of the factors influencing customer interest in using Bank Muamalat products via e-banking. The implications of these findings can help Bank Muamalat KCP Stabat improve its e-banking services to attract more customer interest and increase their satisfaction with the bank's products.